β-NGF Stimulates Steroidogenic Enzyme and VEGFA Gene Expression, and Progesterone Secretion via ERK 1/2 Pathway in Primary Culture of Llama Granulosa Cells - Valderrama, Ximena; Ulloa-Leal, Cesar; Silva, Mauricio Erciario; Goicochea, Jose; Apichela, Silvana; Argañaraz, Martin; Sari, Luciana; Paiva, Luis; Ratto, Vicente Francisco; Ratto, Marcelo Hector (Frontiers in Veterinary Science, 2020)
Nerve growth factor (β-NGF) from llama seminal plasma exerts ovulatory and luteotrophic effects following intramuscular or intrauterine infusion in llamas and alpacas. In this study, we investigated the in vitro effect of llama β-NGF on the expression of genes involved in angiogenesis and progesterone synthesis, as well as progesterone release in preovulatory llama granulosa cells; we also determined whether these changes are mediated via ERK1/2 signaling pathway. From adult female llamas, we collected granulosa cells from preovulatory follicles by transvaginal ultrasound-guided follicle aspiration, these cells were pooled and incubated. After 80 % of confluence, the cultured granulosa cells were treated with β-NGF, β-NGF plus the MAPK inhibitor U0126, or LH, and the abundance of angiogenic and steroidogenic enzymes mRNA transcripts were quantified after 10 and 20 h by RT-qPCR. We also quantified the progesterone concentration in the media after 48 h by radioimmunoassay (RIA). We found that application of β-NGF increased the abundance of mRNA transcripts of the Vascular Endothelial Growth Factor (VEGF), and the steroidogenic enzymes cytochrome P450 side-chain cleavage (P450scc/ CYP11A1), steroidogenic acute regulatory protein (STAR), and 3β-hydroxysteroid dehydrogenase (HSD3B1) at 10 and 20 h of treatment. Application of the MAPK inhibitor U0126 resulted in downregulation of the genes encoding these enzymes. β-NGF also enhanced progesterone synthesis, which was prevented by the prior application of the MAPK inhibitor U0126. Finally, western blot analysis confirmed that β-NGF activates ERK1/2 signaling pathway. In conclusion, our results indicate that β-NGF exerts direct luteotropic effects on the llama ovarian tissue via ERK 1/2 pathway.